Sperm Quality and Fecundity of Glass Carp (Cyprinus carpio) Strain Produced in the Rainy and Dry Seasons - Nadia Dara Panggita Wati; Maheno Sri Widodo; Anik Martinah Hariati (Jurnal Penelitian Pendidikan IPA, 2025)
Carp (Cyprinus carpio) is one of the most widely cultivated freshwater fish species worldwide. C. carpio is increasingly widespread with the presence of the C. carpio glass strain. This fish farming is inseparable from the influence of the season. The purpose of this study was to determine the sperm quality and fertility of glass carp strain produced in the rainy season and dry season. The method used in this research is descriptive. This research was conducted for 3 months (April - June 2024). Samples of glass strain carp C. carpio broodstock and research carried out at the Punten Aquaculture Fisheries Installation (IPB), with a total of 12 broodstock (6 males and 6 females with body size between 25-30 cm). The results showed that the sperm of C. carpio glass strain fish produced in different seasons showed different quality. The best sperm quality was produced in the rainy season with motility (70.44%), concentration (26.75 X 109 cells/ml), and viability (79.81%). However, the rainy season produced the highest abnormality (5.53%). Fecundity of C. carpio glass strain fish was highest in the rainy season reaching 10,875 grains. Further research is needed to determine the success of carp larvae in different seasons.